Transforming the seafood supply system: challenges and strategies for resilience - Ingrid Kelling; Marylyn Carrigan; Andrew F. Johnson (Food Security, 2023)
Seafood is a crucial component of global food systems and plays a vital role in healthy diets and future food security, providing essential omega-3 fatty acids and micronutrients as well as incomes and livelihoods to millions of people. However, the seafood supply system is facing multiple contemporary global challenges that threaten its resilience as well as food security, livelihoods and ecological wellbeing. This opinion piece discusses the drivers of transformative change impacting seafood supply chains, with a particular focus on the UK, but the strategies described can be applied to many similarly developed countries. To address the challenges associated with the COVID-19 pandemic, the war in Ukraine, escalating energy costs, climate change, risk management processes, and to ensure food security and resilience, active policy interventions are needed. Three key policy actions that policymakers can focus on are (i) sustainable seafood models, such as regenerative seafood systems and the circular economy, to improve both environmental and human health outcomes and the likelihood of meeting Sustainable Development Goals; (ii) promote local seafood as part of national food security to strengthen supply chains, support local communities, and enhance traceability and transparency; and, (iii) promote diversification in seafood sourcing and distribution to reduce pressure on critical stocks and increase the flexibility of food systems, while ensuring social and ecological protection. Building a more resilient and sustainable food system requires a holistic and integrated approach, alongside proactive collaboration, to address the multiple, complex, and long-term challenges facing the wider food system.